INCREASING STUDENTS’ VOCABULARY BY USING ANKI-FLASHCARD (A STUDY CONDUCTED AT SMP BEREA TONDANO) - Andrea Junifer Nender; Meity Muntuuntu; Paula Rombepajung (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this research is to find out whether using Anki-flashcard can increase students' vocabulary as a learning-teaching aid in learning English. The object of this research was grade 7th students consisted of 20 students at SMP Berea Tondano. This was quantitative research of pre-test and post-test with pre-experimental design. The data pre-test and post-test were collected using 20 items multiple-choice test. The results of this research indicate that there was a significant difference between the pre-test and post-test. The results of mean score showed improvement between the pre-test (53) and the post-test (90), with the post-test score higher than the pre-test. Therefore, it can be said that the use of the Anki-Flashcard was effective in increasing students' vocabulary. English teachers were suggested to use Anki-Flashcard in teaching and learning to help students remember words more easily.